Immunological analysis of the aqueous humour in candida endophthalmitis. II: Clinical study. Issue 4 (April 1988) - Mathis, A.; Malecaze, F.; Bessieres, M. H.; Arne, J. L.; Seguela, J. P.; Bec, P.
Abstract : An anterior chamber paracentesis was carried out on six patients with candida endophthalmitis and on control subjects. We endeavoured to find out if there was local production of antibodies by evaluating the anti-candida antibody titres, the immunoglobulin G, and the albumin levels in the aqueous humour and in the serum. A significant difference in the level of specific antibodies between patients and controls was found. Local synthesis of anti-candida antibodies was discovered in five out of six patients with candida endophthalmitis. There would seem to be a correlation between the severity of uveitis and antibody titres.